(untitled) (International Journal of Biology and Chemistry, 2015)
This paper reports the study of hydrogen peroxide decomposition and oxidation of cyclohexane catalyzed by polymerprotected gold nanoparticles (AuNPs) immobilized within polyacrylamide hydrogel. The stabilization of AuNPs was achieved using nonionic, anionic and cationic polymers. embedding of AuNPs stabilized with various polymers into polyacrylamide hydrogels was carried out using threeways: «in situ» polymerization, sorption and boronhydride methods. Size, shape and morphology of AuNPs were characterized by various physicochemical methods. Application aspects of polymer-protected AuNPs in catalysis are outlined.